A Proclamation Against Steelets, Pocket Daggers, Pocket Dagges and Pistols (R. Barker printer 1616). - (:unkn) unknown (General Publisher, 1616)
Banned the wear, carry, manufacturer, or sale of steelets, pocket daggers, pocket daggs, & pistols.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION